2018
DOI: 10.1007/s00394-018-1643-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic consumption of a low calorie, high polyphenol cranberry beverage attenuates inflammation and improves glucoregulation and HDL cholesterol in healthy overweight humans: a randomized controlled trial

Abstract: Purpose We studied the health benefits of low calorie cranberry beverage consumption on glucoregulation, oxidative damage, inflammation, and lipid metabolism in overweight but otherwise healthy humans. Methods 78 overweight or obese men and women (30-70 years; BMI 27-35 kg/m 2 ) with abdominal adiposity (waist: hip > 0.8 for women and > 0.9 for men; waist: height ≥ 0.5) consumed 450 mL placebo or low calorie, high polyphenol cranberry extract beverage (CEB) daily for 8 week in a randomized, double-blind, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 60 publications
1
49
1
1
Order By: Relevance
“…This was in line with null findings of another study by Lee et al (11) . However, null findings from these two studies were in contrast to other cranberry studies (6,7,9) . In a study conducted by Shidfar et al (9) , drinking one cup of cranberry juice daily for 12 weeks lowered fasting glucose by approximately 1•1 mmol/l (20 mg/dl) among fifty-eight men with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This was in line with null findings of another study by Lee et al (11) . However, null findings from these two studies were in contrast to other cranberry studies (6,7,9) . In a study conducted by Shidfar et al (9) , drinking one cup of cranberry juice daily for 12 weeks lowered fasting glucose by approximately 1•1 mmol/l (20 mg/dl) among fifty-eight men with type 2 diabetes.…”
Section: Discussioncontrasting
confidence: 89%
“…Cranberries are rich in polyphenols and thus have a high antioxidant capacity, potentially providing health benefits to humans (2) . Studies with cranberry consumption over 2-12 weeks in healthy adults have demonstrated improvement in lipids, blood pressure and biomarkers of oxidative stress (3)(4)(5)(6)(7)(8) .…”
mentioning
confidence: 99%
“…According to Hartog et al Culture of eating is an important factor in the process to receive new product. The new product will be more easily accepted if the product is considered to be in accordance with a strong concept of what can be eaten and technically applicable in the region [17] [18]. Similar thing is also reported by [19][20] [21], the higher a person's compliance to take part in a research program, the higher the increase for the final outcome of the intervention, and vice versa.…”
Section: Biscuit Consumption Compliancesupporting
confidence: 73%
“…For example, one result of this type of bias is that cranberry complex carbohydrates are likely to be unrecognized but significant contributors to the immune-related and cardiometabolic health benefits associated with cranberry materials [3,7,14,17,309]. The fermentation of cranberry complex carbohydrates may lead to beneficial microbiota profiles and SCFA production [74,131,132] that, together, promote epithelial cell health and cholesterol lowering effects as has been observed for other dietary fibers [165,187,189,303].…”
Section: Recognized Composition Influences Bioactivity Interpretationsmentioning
confidence: 99%
“…Decreases in bile acid levels have been associated with the cholesterol-lowering effects of certain foods, such as oats, and with the detoxification of harmful and carcinogenic metabolites [126,187,189,304]. Investigations of other dietary fibers have indicated that fiber viscosity may influence bile acid binding and subsequent cholesterol lowering effects [189] and the high viscosity of soluble cranberry pectins [139] may therefore contribute to the bile acid binding and cholesterol lowering effects observed for cranberry materials [7,154,309].…”
Section: Recognized Composition Influences Bioactivity Interpretationsmentioning
confidence: 99%